The Obama effect : multidisciplinary renderings of the 2008 campaign - Harris, Heather E.; Moffitt, Kimberly R.; Squires, Catherine R., 1972- (State University of New York Press, 2010)
Annotation The editors place Barack Obama's presidential candidacy & 2008 victory in the context of the American experience with race & the media.
Keywords: Obama, Barack -- Influence.; Obama, Barack; Political campaigns -- United States.; Presidents -- United States -- Election -- 2008.; Race relations in mass media.; United States -- Race relations -- Political aspects.; Relations raciales dans les médias.; États-Unis -- Relations raciales -- Aspect politique.; African American Studies.; Ethnic Studies.; SOCIAL SCIENCE.; Influence (Literary, artistic, etc.); Political campaigns; Presidents -- Election; Race relations in mass media; Race relations -- Political aspects; United States; 2008; Electronic books.